A detailed inside look into scribe leadership program of Augmedix BD Ltd- A unique career opportunity of the 21st century - Sami, Raisa (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.